A white pepper decorticator - Shamsudin, Rosnah; Hasaman, Norfarahin; Mohd Adzahan, Noranizan (2013)
The present invention relates to a white pepper decorticator machine comprising: a frame structure (101); a hopper (103) to receive pepper berries; an auger (105) having a thread inside connecting a shaft (106); a rubbing mechanism (107) including a casing (107aa) to rub the pepper berries, the auger (105) and the rubbing mechanism (107) are mechanically operated by first motor (108) and having first power switch (106); a sieving mechanism (109); an water tank (111) including a pump (111a); first sieve(111b); and a water container (111c) to store water for recycling; characterized in that the rubbing mechanism (107) further comprising: first disc (107a) paired with second disc (107b), the two discs having a space in between to allow the pepper berries to be rubbed; and first outlet (107c) as exit for the rubbed pepper berries to the sieving mechanism (109).